Frontispiece: Room‐Temperature Laser Synthesis in Liquid of Oxide, Metal‐Oxide Core‐Shells, and Doped Oxide Nanoparticles. Issue 42 (27th July 2020) - Amendola, Vincenzo; Amans, David; Ishikawa, Yoshie; Koshizaki, Naoto; Scirè, Salvatore; Compagnini, Giuseppe; Reichenberger, Sven; Barcikowski, Stephan
Abstract : Laser synthesis of colloids emerged in recent years as a versatile approach to access a library of clean oxide nanoparticles relying on only four main strategies running at room temperature and ambient pressure: laser ablation in liquid, laser fragmentation in liquid, laser melting in liquid and laser defect‐engineering in liquid. Here, established laser‐based methodologies are reviewed through the presentation of a panorama of oxide nanoparticles. For more information, see the Review by V. Amendola, S. Barcikowski et al. on page 9206 ff.